Analisis Metode Penyederhanaan Kaidah Bahasa Arab dalam Kitab Durusullughah Jilid 1 pada Siswi SMP Muhammadiyah 3 Banjarmasin - Rahman, Fuad; Falah, Mega Satria Nurul (Pusdikra Publishing, 2026)
Arabic is the primary language of Islamic sources; therefore, mastering it is essential for students in Islamic schools. However, Arabic language learning, particularly grammatical rules (nahwu and sharf), is often perceived as difficult due to its complex and theoretical presentation. This study aims to analyze the implementation and effectiveness of the simplified Arabic grammar method derived from Durusullugah Volume 1 by Dr. V. Abdur Rahim in improving the understanding of ninth-grade female students at SMP Muhammadiyah 3 Banjarmasin.This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest model. The research subjects were ninth-grade female students at SMP Muhammadiyah 3 Banjarmasin. Data collection techniques included learning achievement tests (pretest and posttest), student response questionnaires, observation, and documentation. Data were analyzed by comparing students’ learning outcomes before and after the implementation of the simplified grammar method.The results indicate that the application of the simplified Arabic grammar method from Durusullugah Volume 1 significantly improved students’ understanding of Arabic grammar. Furthermore, students showed positive responses toward the method, as the material was presented in a simpler, clearer, and more practical manner. Therefore, the simplified grammar method can be considered an effective alternative approach for enhancing Arabic grammar comprehension at the junior high school level.